PENGARUH KEPEMIMPINAN SPRITUAL DAN NILAI PERSONAL TERHADAP DISIPLIN DAN KINERJA PEGAWAI BIROKRASI - Runtuk, Julianus (Universitas Cenderawasih, 2015)
Researches on leadership are constantly increasing. In particular, in modern leadership, which is the leadership of the humanistic approach, have been widely discussed, especially in a country that facing many social problems. In the reform era, bureaucratic organization, in this case are the government agencies, are required to improve its performance. Nevertheless, the researches that focus on bureaucratic organization (government) are still limited and tend to employ traditional leadership perspectives. This study examines the influence of spiritual leadership and personal value to the discipline and performance of employees in Sarmi County-Papua. The findings will give directions to the local government in managing better and credible public services. Keywords: humanistic leadership, spiritual leadership, personal values, discipline and performance of employees, bureaucratic organization (government)